The rabbit as a surgical model for early training stages of the laparoscopic Nissen fundoplication technique - Rodríguez-Alarcón, Carlos Arturo (2019)
This study describes the advantages and disadvantages of using the rabbit as an animal model for surgical training in the Nissen laparoscopic fundoplication technique. Six New Zealand rabbits weighing between 2.5 and 3.5 kg were used. Nissen fundoplication was performed successfully in five out of six animals. Average procedure time was 47 minutes, with a maximum of 80 minutes for the first surgery and a minimum of 30 minutes for the last. Main advantages of the rabbit model are ease of animal restrain and low cost. The rabbit allows for the recreation of the human surgical environment, albeit showing a lower degree of difficulty. We thus consider this surgical model to be valuable only for skill development on basic stages of the laparoscopic Nissen fundoplication technique. For advanced stages of this surgical procedure, use of other animal models with further anatomical similarities to humans, such as the swine model, are recommended.